2020
DOI: 10.1007/s00270-020-02678-0
|View full text |Cite
|
Sign up to set email alerts
|

FairEmbo Concept for Arterial Embolizations: In Vivo Feasibility and Safety Study with Suture-Based Microparticles Compared with Microspheres

Abstract: Purpose: Microspheres are effective embolic agents especially for the management of bleeding and oncologic lesions. The first FairEmbo study reported the effectiveness of embolization using suture fragments. The effectiveness and safety of arterial embolization with Suture-Based Microparticles (SBM) were assessed in a swine model. Materials and methods:In this ethical-approved animal study, a polar artery in each kidney was embolized in four swine: one side with hand-cut non-absorbable SBM (Flexocrin 2 ® ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The feasibility of using suture fragments has been demonstrated in previous preclinical studies and through a clinical case reported in 2020 [ 10 , 11 , 12 ]. This study demonstrated the feasibility and efficacy of suture embolization through a new and previously untested application: uterine artery embolization in a female porcine model in which the uterine arteries were stimulated by gonadotropin hormone administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of using suture fragments has been demonstrated in previous preclinical studies and through a clinical case reported in 2020 [ 10 , 11 , 12 ]. This study demonstrated the feasibility and efficacy of suture embolization through a new and previously untested application: uterine artery embolization in a female porcine model in which the uterine arteries were stimulated by gonadotropin hormone administration.…”
Section: Discussionmentioning
confidence: 99%
“…The FairEmbo concept aims to make available a worldwide, effective, and safe embolization agent, either using absorbable or non-absorbable sutures. It has recently demonstrated that embolization with suture fragments is feasible and effective in short- and medium-term follow-up in porcine models [ 10 , 11 ]. Its clinical efficacy was also demonstrated by clinical case emergency embolization of a renal artery pseudoaneurysm in 2020 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One key to solve the problem may be ''technique''. The paper, ''FairEmbo concept for arterial embolizations: In vivo feasibility and safety with suture-based microparticles compared with microspheres'' introduced the technique of ''cutting the thread into small pieces'' and showed the possibility that this technique can reduce the cost of IR [3]. In the current trend where most interventional radiologists hope to use expensive and high quality imaging equipment and devices, the attitude of conducting research and publishing papers from the viewpoint of ''cheaper IR'' is commendable [4,5].…”
mentioning
confidence: 99%